Incidence and risk factors for the development of pulmonary arteriovenous malformations after stage 2 palliation - Lea Behrend; Thibault Schaeffer; Muneaki Matsubara; Jonas Palm; Teresa Lemmen; Nicole Piber; Paul Philipp Heinisch; Stanimir Georgiev; Alfred Hager; Peter Ewert; Jürgen Hörer; Masamichi Ono (International Journal of Cardiology Congenital Heart Disease)
Objective: This study evaluated the current incidence of pulmonary arteriovenous malformations (PAVMs) following stage 2 palliation (S2P). Methods: Patients who underwent S2P, either through a bidirectional cavopulmonary shunt (BCPS) or the Kawashima procedure (KP) between 1992 and 2022, were reviewed. The cumulative incidence of PAVMs was compared between BCPS and KP. Risk factors for the development of PAVMs were identified. Results: Among 682 patients who underwent S2P, 661 (96.9 %) underwent BCPS and 21 (3.1 %) KP. Median age at S2P was 5.1 (interquartile ranges (IQR): 3.6–9.6) months. During the median interstage follow-up of 1.6 (IQR: 1.6–2.2) years, PAVMs developed in 11 (1.6 %) patients (1.1 % (n = 7) after BCPS and 19.0 % (n = 4) after KP). Cumulative incidence of PAVMs was higher in patients after KP than those after BCPS (p < 0.001). PAVMs were observed in the right lung in 9 patients and both lungs in two. One patient with biliary atresia died of progressive PAVMs and liver cirrhosis after KP, and the remaining 10 patients underwent Fontan completion with a median interval of 1.9 (IQR: 1.5–2.4) years. PAVMs improved in all patients (9 resolutions and 1 improved). Independent risk factors for the development of PAVMs were KP (hazard ratio (HR): 16.364, p < 0.001) in all patients, anomalous pulmonary venous connection (HR: 6.772, p = 0.023) in BCPS patients, and hypoplastic left heart syndrome (HR: 18.819, p = 0.018) in KP patients. Conclusions: The incidence of PAVMs after S2P is very low after BCPS but still relevant after KP. Resolution or improvement of PAVMs is probable after Fontan completion.